Answered

Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Solve for [tex]\( x \)[/tex].

[tex]\[ \frac{6 - 5x}{-3x} = \][/tex]


Sagot :

To simplify the expression [tex]\(\frac{6-5x}{-3x}\)[/tex], follow these steps:

1. Distribute the denominator: Notice that both terms in the numerator can be divided by the common denominator.

[tex]\[ \frac{6-5x}{-3x} = \frac{6}{-3x} - \frac{5x}{-3x} \][/tex]

2. Simplify each fraction separately:
- For the first fraction [tex]\(\frac{6}{-3x}\)[/tex]:

[tex]\[ \frac{6}{-3x} = \frac{6}{-3} \cdot \frac{1}{x} = -2 \cdot \frac{1}{x} = -\frac{2}{x} \][/tex]

- For the second fraction [tex]\(\frac{5x}{-3x}\)[/tex]:

[tex]\[ \frac{5x}{-3x} = \frac{5}{-3} \cdot \frac{x}{x} = -\frac{5}{3} \cdot 1 = -\frac{5}{3} \][/tex]

3. Combine the simplified terms:

[tex]\[ \frac{6-5x}{-3x} = -\frac{2}{x} - \frac{5}{3} \][/tex]

4. Rearrange the terms to match a more conventional format (if required). Instead of leaving a negative sign for each term, we can combine them into a single expression:

[tex]\[ \frac{6-5x}{-3x} = -\left(\frac{2}{x} + \frac{5}{3}\right) \][/tex]

This can also be written as:

[tex]\[ \frac{6-5x}{-3x} = \frac{5}{3} - \frac{2}{x} \][/tex]

Therefore, the simplified form of the given expression is:

[tex]\[ \frac{6-5x}{-3x} = \frac{5}{3} - \frac{2}{x} \][/tex]